Online assay of bone specific alkaline phosphatase with a flow injection-bead injection system - Hartwell S.K. (2014)
Alkaline phosphatase (ALP) has been used as one of the biomarkers for bone resorption and liver diseases. Normally, total alkaline phosphatase is quantified along with other symptoms to determine the releasing source of the alkaline phosphatase. A semi-automated flow injection-bead injection system was proposed to conveniently and selectively assay bone alkaline phosphatase (BALP) based on its specific binding to wheat germ coated beads. Amount of BALP in serum was determined from the intensity of the yellow product produced from bound BALP on the retained beads and its substrate pNPP. The used beads were discarded and the fresh ones were introduced for the next analysis. The reaction cell was designed to be opened and closed using a computer controlled solenoid valve for a precise incubation time. The performance of the proposed system was evaluated by using it to assay BALP in human serum. The results were compared to those obtained by using a commercial ELISA kit. The system is proposed to be an easy and cost effective system for quantification of BALP as an alternative to batch wise wheat germ specific binding technique. © 2007 Elsevier B.V. All rights reserved.